(untitled) (The International Journal for Scientific Research, 2024)
Background: The reported prevalence rates of hydatidiform mole (HM) vary greatly across geography and time, making worldwide comparisons challenging, especially in developing countries and resource-limited settings. To date, few studies have been reported in Yemen regarding the epidemiology, management, and outcome of patients with HM. The current study sought to investigate the prevalence of HM among women who visited a large tertiary center at Jiblah University Hospital in Yemen. Method: A retrospective study was conducted between Jun 2017 and Sep 2022 at Jiblah University Hospital, Ibb, Yemen including all women with a diagnosis of HM. Complete medical histories for all HM patients were collected and analyzed. Results: A total of 160 women diagnosed with HM at Jiblah University Hospital -Ibb study from 2017 to 2022 years were included in the study. The mean gestational age on admission was 25.2 years. Sixty-two patients (38.7%) have Hb less than normal range and 94 of patients (58.8 %) have Hb normal range 12- 15g/dl and 4 patients (2.5 %) have Hb more than normal range 15g/dl. However, the percentage blood types (A+, A-, B-, B+, O+, O- and AB+) were 40.6%, 0.6%, 5%, 0.6%, 41.9 %, 7.5% and 3.8%, respectively. On the other hand, among the sample, 4 (2.5%) women were diagnosed histopathologically to have previous V.M and while 156 (97.5%) women were diagnosed histopathologically to have no previous V.M. A number of women who had previous abortion were recorded 46(28.7%) and while the women had not previous abortion was 114(41.4%). Among the women who had smoking and no smoking were recorded 2(1.3%) and 158(98.7%), respectively. Finally, unfortunately the researchers didn’t find following risk factors in the register of patients, such as (Ovulation induction, genes mutation, infertility and birth control pills), by researching the record of patients with HM or registered as having HM. However, our study found the relationship between age groups and the previous abortion about associate risk factors of molar pregnancy. There is statistically significant difference between previous abortion and age, with P-value =0.007. Conclusion: The present study showed that incident hydatidiform mole were higher in 20-29 years of maternal age, so we found that the incidence of HM in younger age patients is the most common. Also, we found that the significant positive correlation was found between age with previous abortions. Therefore, it is recommended that women should undergo health care before pregnancy and further studies are required to provide solutions to reduce the cases of HM.